Identification of Enhancer RNA CDK6-AS1 as a Potential Novel Prognostic Biomarker in Gastric Cancer - Yang, Shifeng; Zou, Xiaoming; Yang, Hao; Li, Jiacheng; Zhang, Ange; Zhang, Lisha; Li, Changjian; Zhu, Lei; Ma, Zhen (Frontiers in Genetics, 2022)
Background: The aim of this study was to confirm enhancer RNAs (eRNAs) in gastric cancer and its clincial utility. Methods: We used cox survival analysis and relevance analysis to identify the candidate eRNAs in gastric cancer. Moreover, we performed GO and Reactome pathway enrichment to found the potential functions of eRNAs.Correlation between eRNA, tumor-infiltrating immune cells and drug sensitivity was then analyzed. Results: CDK6-AS1 may serve as a poor independent prognostic biomarker candidate in gastric cancer with positive correlation with its target gene CDK6. Low CDK6-AS1 expression group showed more frequent mutated driver genes than high expression ones. Moreover, CDK6-AS1 is involved in key oncogenic pathway as cell cycle and RNA transcription. CDK6-AS1 also shows dysregulations and associations with prognosis at pan-cancer level. This eRNA may also associated with immune cell infiltration and drug sensitivity. Conclusion: CDK6-AS1 may be a potential prognostic biomarker for gastric cancer, predict chemotherapeutic drugs sensitivity of gastric cancer.